Trabectedin – the DNA minor groove binder - G. A. Belitsky; K. I. Kirsanov; E. A. Lesovaya; M. G. Yakubovskaya (Успехи молекулярной онкологии, 2015)
Trabectedin (ET-743, Yondelis) is an alkaloid that was originally isolated from the Caribbean Sea squirt, Ecteinascidia turbinata and is now produced synthetically. Its chemical structure consists in three fused tetrahydroisoquinoline rings. Two of them, A and B, binds covalently to guanine residues in the minor groove of the DNA double helix to bend the molecule toward the major groove and the third ring C protrudes from the DNA duplex, apparently allowing interactions with several nuclear proteins. Binding to the minor groove of DNA, trabectedin trigger a cascade of events that interfere with several transcription factors, DNA binding proteins, and DNA repair pathways in particular nucleotide excision repair. It acts both as a DNA-alkylating drug and topoisomerase poison. Trabectedin-DNA adduct traps the nucleotide excision repair proteins repairing the DNA damage in transcribing genes and induces DNA strand breaks. Cells deficient in homologous recombination pathway which repairs these double-strand breaks show increased sensitivity to trabectedin. The most sensitive of them were myxoid liposarcomas. Trabectedin is also effective in chemotherapy-experienced patients with advanced, recurrent liposarcoma or leiomyosarcoma as well as in women with ovarian cancer and breast cancer with BRCAness phenotype. Besides of tumor cells Trabectedin inhibits inflammatory cells by affecting directly monocytes and tumorassociated macrophages and indirectly by inhibiting production of inflammatory mediators, the cytokines and chemokines. It inhibits also the MDR-1 gene, which is responsible for the resistance of cancer cells to chemotherapeutic agents and strikes tumor angiogenesis.